Management Control System, Innovation Dan Organizational Performance - Risman Nursyamsir; Tubagus Ismail; Iis Ismawati (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of the management control system on organizational performance mediated by the management innovation variable, where the management control system is combined with two different control levers the enabling (beliefs and interactive) and the constraining (boundary and diagnostic), and management innovation which consists of four dimensions (new management practice, management process, organizational structure, and management technique). The method used in this research is quantitative. The research sample uses primary data by distributing questionnaires. There are 9 Regional Apparatus Organizations that are sampled in this study based on predetermined criteria (purposive sampling). Data analysis was performed by path analysis using the WarpPLS 7.0 program. The results showed that the management control system enabling and the management control system constraining have a positive effect on organizational performance. And management control system enabling and management control system constraining positive effect on management innovation Meanwhile, management innovation has a partial effect, where organizational structure has a negative effect on organizational performance and management techniques have a positive effect on organizational performance. Meanwhile, new management practices and management processes have no effect on organizational performance.